Correlation study between organizational antecedent with job satisfaction, work performance and knowledge sharing practices - Abdullah, Nurfarahin Jasmine See; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This research is to determine correlation between organization antecedent, job satisfaction, work performance and knowledge sharing practice among academician at Malaysia Research Universities. The hypothesis for this research are organization antecedent has correlation with job satisfaction, work performance and knowledge sharing practice. The variables in this research are organizational antecedent which consist of people, organization and technology, as for job satisfaction consist of job, salary, promotion, supervision and co-worker while as work performance consist of work, ability, discipline, relationship and innovation and for knowledge sharing practice consist of socialization, externalization, combination and internalization. Applying the theory of multiple perspective for organizational antecedent, theory of needs for job satisfaction and work performance and SECI for knowledge sharing practice. The data analysis measured for Correlation Coefficient (r) for relationship effected either positive or negative and the level of relationships that are low, moderate or high. The findings show support the hypothesized relationship proposed and the results are most positively moderate level of relationship.